PATHOGENICITY STUDIES OF A FUNGUS ASSOCIATED WITH Tetranychus urticae Koch YUCCA PLAGUE MITE - ALVAREZ, JUAN MANUEL; BELLOTII, ANTHONY C.; BRAUN, ANN R.; ACOSTA, ALFREDO (Revista Colombiana de Entomología, 1991)
The two-spotted spider mite, Tetranychus urticae Koch, is a pest that causes considerable losses in the cassava crop (Manihot escuelenta Crantz). However, there have been detected epizootics that affect its populations. To determine the epidemic causes, laboratory studies were carried out attempting to infect healthy mites. Also, daily observations were done with the disecting microscope registering the disease symptoms. Finally, mites were mounted on slides to be examined using phase-contrast microscopy in order to confirm the presence of the fungal pathogen and its identification. The results indicated that reinfection could occur when a healthy mite and an infected one were put together under 100% R.H. and a temperature of 26°C. The symptoms consisted of changes in their natural body color, sluggish movements, death, mummification, and sometimes invasion by secondary pathogens; in addition, during this process, infected mites increased their volume (swollen bodies). Each one of their symptoms was related to a developmental stage of a fungus, which was identified as beloging to the genus Entomophthora.